English teachers’ motivation for a professional development program: Perspectives of self-determination theory - Basikin, B. (Indonesian Journal of Applied Linguistics, 2020)
The externally driven motivation for a teacher professional development (PD) program is considered less favorable in achieving the desired outcomes than the internally-driven one. When the PD involves a large number of participants, not achieving the outcome leads to a significant waste of time, money, and energy. Unfortunately, this is a common condition in the Indonesian context where teachers go to a PD program due to external motivation. This study examines school English teachers’ motivation to attend a PD program in the Yogyakarta province of Indonesia recruited in their district teacher forum (MGMP) meetings. It seeks to answer whether or not externally driven motivation or controlled motivation might become more autonomous. Following the framework of the Self-determination Theory, teachers’ motivation was measured using the Teacher Motivation for a Professional Development Scale (TMPDS). Findings suggest that although participants still perceived externally driven attendance by reporting high scores on both introjected regulation (M = 5.73; SD = 2.28) and external regulation  (M = 6.51; SD = 1.54), they also reported high on their intrinsic motivation (M = 7.58; SD = 1.08 ) and the identified regulation (M = 7.91; SD = 1.04). Findings indicate that initial extrinsic motivation or controlled could become more intrinsic or autonomous depending on the levels of internalization among the individuals. Findings imply when motivation is external, PD programs should make sure that autonomy supports are available to facilitate internalization.